2005
DOI: 10.1677/joe.1.06211
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of the novel adipocytokine visfatin in 3T3-L1 adipocytes

Abstract: Recently, visfatin was characterized as a novel adipocytokine that is upregulated in obesity and exerts insulinmimetic effects in various tissues. To clarify expression and regulation of this adipocytokine, visfatin mRNA was measured by quantitative real-time reverse transcriptionpolymerase chain reaction in 3T3-L1 adipocytes during adipogenesis and after treatment with various hormones known to alter insulin sensitivity. Visfatin expression was about 6-fold higher in 3T3-L1 adipocytes in vitro as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
93
8
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 41 publications
(46 reference statements)
12
93
8
4
Order By: Relevance
“…In cultured adipocytes there was little if any impact of glucose on visfatin release when insulin was present and this effect was fully restored by insulin-receptor blockade. This is consistent with findings from other studies demonstrating that insulin alone had no effect on unstimulated 3T3-L1 adipocytes [17]. Although the physiological actions of visfatin are as yet poorly understood, the negative regulation of hyperinsulinaemia may affect circulating visfatin concentrations in patients with diabetes mellitus type 2 or insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In cultured adipocytes there was little if any impact of glucose on visfatin release when insulin was present and this effect was fully restored by insulin-receptor blockade. This is consistent with findings from other studies demonstrating that insulin alone had no effect on unstimulated 3T3-L1 adipocytes [17]. Although the physiological actions of visfatin are as yet poorly understood, the negative regulation of hyperinsulinaemia may affect circulating visfatin concentrations in patients with diabetes mellitus type 2 or insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on 3T3-L1 adipocytes have demonstrated that visfatin is regulated by hormones and cytokines influencing glucose homeostasis [17,18]. A surprising finding of our studies was the negative feedback of insulin on glucoseinduced visfatin release.…”
Section: Discussionmentioning
confidence: 52%
“…It is likely that increased growth hormone secretion together with concurrent training has caused visfatin secretion. As Tayebi stated in animal studies, growth hormone causes suppression of visfatin gene expression in adult cells secreting visfatin (38).…”
Section: Discussionmentioning
confidence: 93%
“…Although at 90 minutes after exercise the plasma insulin level of the glucose group was higher than that of the water group, but the difference was not significant. It has been shown that insulin does not affect visfatin synthesis in adipocytes, and no significant difference has been observed in the serum visfatin levels of diabetic patients and those who injected insulin or received hypoglycemic agents (23,24). In addition, the effect of insulinsensitizing agents on serum visfatin has not yet been confirmed (25,26).…”
Section: Discussionmentioning
confidence: 98%